Computational Studies on the Reactivity of Polycyclic Aromatic Hydrocarbons. Issue 6 (9th December 2022) - Su, Yingwei; Ren, Qing; Zhang, Wen‐Yan; Chen, Feiwu
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widely present in the environment as toxic pollutants. In this study, quantum chemistry methods are used to study reactions of PAHs in both particle and gas phases. Seven theoretical methods are exploited to predict the reactive sites of 15 PAHs in the particle phase. Among these methods, the performance of the condensed Fukui function (CFF) is optimum. The gas‐phase reactions of eight PAHs are also investigated. Except for fluorene, CFF predicts correctly the gas‐phase mono‐nitro products for seven systems. The products of fluorene predicted by CFF are 1‐nitrofluorene and 3‐nitrofluorene, which is however inconsistent with the experimental results. Transition state theory is then used to investigate the reaction mechanism of fluorene. Calculated rate constants for 3‐nitrofluorene and 2‐nitrofluorene formation are much bigger than that for 1‐nitrofluorene formation, which is in agreement with the experimental results. Abstract : Predicting reaction pathways : Wavefunction analysis and transition state theory are powerful approaches for predicting the active reaction sites and reaction pathways of polycyclic aromatic hydrocarbon in both gas and particle phases.